Madrasah Teachers' Engagement in Promoting Religious Moderation - Rahman, Mohammad Taufiq; Mulyana, Mulyana (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
This article examines the patterns of teacher participation in supporting religious moderation programs at the madrasah level. The participation process itself is inseparable from the position of teachers as the center of students' activities in imparting and receiving knowledge and information about religious moderation. The study, conducted in two madrasahs with different religious orientations in Bandung and Garut regencies, employs a qualitative method with data collection techniques including observation, interviews, documentation study, and case study. The research findings indicate the existence of a participation activity model characterized by organizers, participants, and supporters of religious moderation activities based on Islamic teachings principles. Other madrasahs should exemplify this to strengthen the character, attitudes, and openness of students in facing the pluralistic religious developments in society.